2012
DOI: 10.1128/aac.01080-12
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Is Superior to Vancomycin in Experimental Pneumonia Caused by Superantigen-Producing Staphylococcus aureus in HLA Class II Transgenic Mice

Abstract: Superantigens (SAg), the potent activators of the immune system, are important determinants of Staphylococcus aureus virulence and pathogenicity. Superior response to SAg in human leukocyte antigen (HLA)-DR3 transgenic mice rendered them more susceptible than C57BL/6 mice to pneumonia caused by SAg-producing strains of S. aureus. Linezolid, a bacterial protein synthesis inhibitor, was superior to vancomycin in inhibiting SAg production by S. aureus in vitro and conferred greater protection from pneumonia cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…None of the mice (4-5 mice in each group), either treated with antibodies or left untreated succumbed to pneumonia. This study reaffirmed our earlier report that SAg (SEB in our model) plays a lethal role in pneumonia 54 Moreover, this result also demonstrated that these antibodies are safe and do not potentiate pneumonia caused by S. aureus that do not produce any SAg. In the final set of experiments, we wished to establish the specificity of anti-SEB monoclonal antibodies and to verify that these chimeric antibodies do not have any non-specific antistaphylococcal activity.…”
Section: Humanized Anti-seb Antibodies Protect From Lethal Pneumoniasupporting
confidence: 92%
See 2 more Smart Citations
“…None of the mice (4-5 mice in each group), either treated with antibodies or left untreated succumbed to pneumonia. This study reaffirmed our earlier report that SAg (SEB in our model) plays a lethal role in pneumonia 54 Moreover, this result also demonstrated that these antibodies are safe and do not potentiate pneumonia caused by S. aureus that do not produce any SAg. In the final set of experiments, we wished to establish the specificity of anti-SEB monoclonal antibodies and to verify that these chimeric antibodies do not have any non-specific antistaphylococcal activity.…”
Section: Humanized Anti-seb Antibodies Protect From Lethal Pneumoniasupporting
confidence: 92%
“…We had previously reported that the S. aureus strain IDRL-7419 which produces SEB, but not its isogenic counterpart IDRL-7420 that does not produce SEB, causes lethal pneumonia in HLA-DR3 transgenic mice. 54 We had also demonstrated that this is due to higher susceptibility of HLA-DR3 transgenic mice to the immune-stimulating effects of SEB compared with C57Bl/6 mice. 54 To specifically show that SEB produced by the S. aureus strain IDRL-7419 causes early and robust activation of T cells during pneumonia, we generated HLA-DR3.Nur77-eGFP transgenic mice.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…IDRL-7971 is a methicillin-susceptible S. aureus clinical isolate producing SEA and SEB [16,22]. The S. aureus strain RN6734 contains the intact cloned seb pRN5543::seb (pRN7114) and produces SEB (referred to as SEB + SA).…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…After 48 hours, 1 mg tritiated [ 3 H]thymidine was added, and the cells were incubated for an additional 18 hours. The extent of proliferation was determined by measuring incorporated radioactivity [16,22].…”
Section: Splenocyte Proliferation Assaymentioning
confidence: 99%